Students training for WWI, Fletcher Field, circa 1913 - Munro, Melville S. (Tufts Archival Research Center, 2005)
8.25 x 4.5, mounted on 8 x 10 in: M. S. Munro, Miscellaneous pictures through the years, Vol. 1, p. 28. A Student Company was formed in anticipation of our entering the World War and used the old campus (Fletcher Field) as a training field